Rural-urban transformation shapes oasis agriculture in Morocco’s High Atlas Mountains - Youness Boubou; Kira Fastner; Andreas Buerkert (Scientific Reports)
Abstract Traditional agricultural activities and rural livelihoods in Morocco’s High Atlas Mountains are rapidly changing. This is triggered by increasing rural-urban interactions and new livelihood opportunities in cities. A typical example is the oasis of Tizi N’Oucheg in the country’s High Atlas Mountains, which over centuries was largely self-sufficient in food grain and livestock production. Improved infrastructure and better connections to distant urban centers have caused declining livelihood reliance on agricultural activities and enhanced dependence on remittances and the tourism sector in the region. Based on the case of Tizi N’Oucheg, this study aims at assessing the socio-economic and ecological implications of rural-urban transformation for ancient oasis systems in Morocco. Surveys on agricultural practices, census, and meteorological data were combined with GIS (Geographical Information System) -based analyses to examine land use and cropping pattern changes of 625 fields from 1967 to 2022. For the GIS analyses, historical aerial images, multispectral satellite images, and drone-based surveys were used to generate manually classified agricultural fields and NDVI (Normalized Difference Vegetation Index) time series. Our results show a major decline in cultivated land from 13 ha to 6.8 ha over the past 50 years accompanied by an expansion of modern infrastructure since the 2000s. Land management has shifted from labor-intensive multiple cropping and natural fertilization to monocropping of barley for local livestock feeding and increased application of mineral fertilization. The challenging geography of the oasis increased the hardship of practicing traditional agriculture, and therefore largely determines the response of the community to rural-urban transformation. Our data also highlight the increased financial dependence of rural populations on urban centers and the demise of traditional, sustainable agriculture in Morocco’s High Atlas Mountains if policies on agricultural development are not adapted to rural circumstances.